IMPLEMENTASI WEBSITE SEBAGAI MEDIA DIGITAL MARKETING PRODUK TENUN “KAMENZ” TROSO JEPARA - Puri Sulistiyawati; Toto Haryadi; Dimas Irawan Ihya' Ulumuddin (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2023)
Jepara is not only famous on wood carving, but also troso woven fabric products. In recent years, the number of weaving craftsmen has decreased due to the Covid-19 pandemic and the lack of the next generation. This has led to a decrease in the turnover of the Troso weaving business, especially Kamenz Troso which still survives. The use of digital media for product promotion and marketing is only by whatsapp stories and word of mouth, which only cover specific consumers and do not explain about troso products. Digital marketing media is needed which is able to accommodate information, transaction, and communication functions, all of them can be accommodated by a website. This research focuses on website development as a digital marketing medium, through qualitative research methods supported by observation, interview, documentation, and literature studies. Website development applies the Bryan Lawson method. The results of this study are the website as a digital marketing medium that can be accessed via desktop and smartphone, contains information about troso weaving, transaction activities up to payment, and communication facilities in the form of live chat. This research can be developed further, for example towards designing the Kamenz Troso.